Evaluasi Dampak Kualitas Produk dan Pemasaran Konten Skintific Terhadap Keputusan Pembelian Konsumen di Tiktok - Ambotuwo, Fadhlillah Dzil Ikram; Mahmudi, Muhammad Fauzan Adzim Al (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Social media platforms such as TikTok have transformed digital marketing strategies, particularly in the beauty industry. Skintific, a growing skincare brand, leverages creative content on TikTok to build its brand image and attract consumer interest. This study analyzes the influence of product quality and content marketing on consumer purchasing decisions. Using a quantitative approach, questionnaires were distributed to 100 TikTok users who were familiar with and had purchased Skintific products. The data were analyzed using multiple linear regression. The results showed that both variables had a positive and significant influence on purchasing decisions. Content marketing proved to be more dominant in creating initial attraction and building consumer trust. These findings suggest that the combination of superior product quality and creative content marketing can enhance the effectiveness of digital marketing strategies and drive purchasing decisions.